Enhanced corrosion resistance and cell activity of magnesium alloy by DCPD/MgHPO4·3H2O coating via one-step chemical conversion - Wang, Xinxuan; Guo, Liping; Liu, Xuhui; Dai, Yilong; She, Jia; Zhang, Dechuang; Qi, Fugang; Wei, Wenwen; Ouyang, Xiaoping (Surface & coatings technology, 2024)
In order to solve the issue of rapid corrosion in magnesium alloy, composite coating of CaHPO4·2H2O (DCPD) and MgHPO4·3H2O were prepared in one step using chemical conversion method. By changing the pH of phosphating conversion solution, the composite coatings with varying contents of DCPD and MgHPO4·3H2O were prepared, and their components were characterized. An electrochemical test was employed to compare the short-term corrosion properties of different composite coating. The findings revealed that the composite coating possessed the optimal short-term corrosion performance when pH of phosphating solution was 1.8. The long-term corrosion results demonstrated that the composite coatings fabricated at a pH of 1.8 in the phosphating solution, following a 7-days immersion, not only exhibited the optimal long-term corrosion resistance but also possessed the highest biomineralization capacity. This could be attributed to the fact that the composite coating prepared at this pH of phosphating solution possessed a structurally rational design, and MgHPO4·3H2O could play a supportive role in maintaining structural integrity during the degradation process. Indirect cell culture results indicated that at a dilution concentration of 25 %, the cell activity of the coatings, except for Ca-Mg-P3.0, was >75 %, suggesting good biocompatibility. [Display omitted] •The composite coatings are prepared by one step chemical conversion method.•Different composite coatings are prepared by changing the pH of phosphating solution.•Ca-Mg-P1.8 coating possesses the best corrosion performance and non-toxic.•MgHPO4·3H2O coating supports the structural integrity during the corrosion process.